Projected impact of elbasvir/grazoprevir in patients with hepatitis C virus genotype 1 and chronic kidney disease in Vietnam - Chizoba Nwankwo; Shelby L. Corman; Elamin H. Elbasha (Elsevier, 2019)
Background: Hepatitis C virus (HCV) infection is an important cause of morbidity and mortality in patients with chronic kidney disease (CKD). The objective of this study was to predict the impact of EBR/GZR on the incidence of liver and kidney related complications compared with no treatment (NoTx) and pegylated interferon plus ribavirin (pegIFN/RBV) in patients with CKD stage 4/5 in Vietnam. Methods: We developed a mathematical model of the natural history of chronic HCV, CKD, and liver disease. Efficacy of EBR/GZR and pegIFN/RBV were derived from the C-SURFER trial and a meta-analysis, respectively. We calculated lifetime cumulative morbidity and mortality rates, including incidence of decompensated cirrhosis (DC), hepatocellular carcinoma (HCC), and life expectancy. Results: Estimated lifetime incidence of DC was significantly reduced in patients receiving EBR/GZR (3.47%) compared to NoTx (18.14%) and pegIFN/RBV (9.01%). Estimated incidence of HCC was 1.02%, 21.64%, and 8.90%, and 1.02% in patients receiving EBR/GZR, NoTx, and pegIFN/RBV. EBR/GZR was estimated to extend life expectancy by 4.2 and 2.0 years compared with NoTx and pegIFN/RBV. Conclusions: Our model predicted that EBR/GZR will significantly reduce the incidence of liver-related complications and prolong life in patients with chronic HCV GT1 infection and CKD compared with NoTx or pegIFN/RBV. Keywords: Hepatitis C, Chronic kidney disease, Economics, Elbasvir/grazoprevir